Classification of loaded/unloaded micro‐drones using multistatic radar. Issue 22 (13th October 2015) - Fioranelli, F.; Ritchie, M.; Griffiths, H.; Borrion, H.
Abstract : Preliminary results on the use of multistatic radar and micro‐Doppler analysis to detect and discriminate between micro‐drones hovering carrying different payloads are presented. Two suitable features related to the centroid of the micro‐Doppler signature have been identified and used to perform classification, investigating also the added benefit of using information from a multistatic radar as opposed to a conventional monostatic system. Very good performance with accuracy above 90% has been demonstrated for the classification of hovering micro‐drones.